Flora epifítica em fitofisionomias do Parque Estadual do Utinga Camillo Viana, Belém, Pará, Brasil. - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2025)
The objective was to compare the epiphytic flora in vegetation fragments of the Utinga State Park in edge and interior conditions and its influence on the richness and composition of epiphytes. The study was carried out in the Conservation Unit, Utinga Camilo Viana State Park in the city of Belém (PA) with floristic inventories in campinarana, floodplain forest and terra firma forest. The dryland forest was divided into edge conditions (recent and old) and interior conditions (outside the edges) with the minimum distance between sampling points of 50 to 100 meters. The results showed six epiphytes in Campinarana, with Vanilla pompona Schied as the first record for the state of Pará. In the dryland and floodplain forests, 20 and 16 species were identified, respectively. The most important genus was Philodendron with 10 species, with P. guttiferum Kunth and P. Callosum Schott being abundant. The richness of epiphytes was greater in the interior dryland forest compared to recent and old edge conditions. In the floodplain forest, the composition of epiphytes was diferente between the phytophysiognomies. The number of epiphytes was high, demonstrating the importance of conservation in a Conservation Unit vulnerable to recurring anthropogenic impacts in the city of Belém.
Epiphytic flora in phytophysiognomies of the Utinga Camillo Viana State Park, Belém, Pará, Brazil.
Keywords: Florística; Riqueza; Abundância; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA